Long-term effectiveness of behavioural intervention in preschool children with attention deficit hyperactivity disorder in Southeast China - a randomized controlled trial - Xin-xin Huang; Ping Ou; Qin-fang Qian; Yan Huang (BMC, 2021)
Abstract Background Attention-deficit hyperactivity disorder (ADHD) is the most common behavioral disorder. Behavioural intervention in preschool children with ADHD is considered effective. This study discussed the long-term effectiveness of behavioural intervention in the context of nondrug therapy. Methods The study was a prospective, randomised controlled trial in which 201 preschoolers diagnosed with ADHD who were not receiving any treatment were assigned to two groups from January 2018 to May 2019, 101 were assigned to the conventional group and 100 to the behavioural intervention group. The behavioural intervention group included parental training, behavioural therapy, attention training, relief therapy and game therapy, in addition to the conventional group offerings. Children were evaluated at a baseline, at the end of the 12-month intervention and six months after the intervention. The primary and secondary outcome variables included attention time, the impulse-hyperactivity and hyperactivity index from Conners parent symptom questionnaire (PSQ), full-scale attention quotient (FAQ) and full-scale response control quotient (FRCQ) from integrated visual and auditory comprehensive continuous performance tests. The attention time was observed and recorded by parents, and others were performe(PSQ)d by physicians in the clinic. All statistical analyses were conducted using SPSS V26.0 (IBM), including the descriptive statistics and mixed-effects models and so on. Results The participants' mean age was (66.17±9.00) months in the behavioural group and (67.54±6.22) months in the conventional group .A total of 190 participants completed a follow-up six months after the intervention. The attention time, Conners parent symptom questionnaire (PSQ), full-scale attention quotient (FAQ) and full-scale response control quotient (FRCQ) increased significantly over time, and the behavioural group improvements were higher than those of conventional group. There was a significant main effect of time (pretest/posttest/follow-up) and group on all outcome measures (t =-12.549-4.069, p<0.05), and a significant interaction of time and group on attention time, impulsivity/hyperactivity, FAQ and FRCQ (t =-3.600-3.313, p<0.05). Conclusion Behavioural intervention can effectively improve behaviour management and relieve symptoms in children with ADHD. These effects lasted at least six months. This study provides a promising approach for improving clinical efficacy with preschool children with ADHD.